2019
DOI: 10.3390/ma12193066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Y/Er and Zn Addition on the Microstructure and Mechanical Properties of Mg-11Li Alloy

Abstract: Although body-centered cubic (BCC) structural magnesium–lithium (Mg-Li) alloys have lower density and better formability than common hexagonal close-packed (HCP) Mg alloys, their applications remain limited due to their low strength. The purpose of this study is to investigate the effect of Y/Er and Zn addition on the microstructure and tensile properties of Mg-11Li alloy with a BCC structural matrix by comparing Mg-11Li, Mg-11Li-4Y-2Er-2Zn, and Mg-11Li-8Y-4Er-4Zn (wt %) alloys. The results indicate that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…When the dye concentration increases, more reactants and reaction intermediates react with the hydroxyl radicals, leading to an insufficient number of hydroxyl radicals. 35 Therefore, the degradation rate decreased with increasing dye concentration.…”
Section: Factors Affecting Degradation Efficiencymentioning
confidence: 95%
“…When the dye concentration increases, more reactants and reaction intermediates react with the hydroxyl radicals, leading to an insufficient number of hydroxyl radicals. 35 Therefore, the degradation rate decreased with increasing dye concentration.…”
Section: Factors Affecting Degradation Efficiencymentioning
confidence: 95%
“…Alloys with other solute elements such as Zn, Al, Mn, Gd and Sn have also exhibited significant effects on grain refinement and mechanical properties [20], features that can be achieved by alloying and post processing. For example, a remarkable grain size reduction from 300 m to 33 m was achieved via extrusion [21].…”
Section: Design Considerations For Mg-li Based Alloysmentioning
confidence: 99%
“…The increase in strength was attributed to precipitation strengthening, and formation of twins and stacking faults whereas the increase in ductility was ascribed to the gradual dissolution of Mg25(Gd, Y)5 at grain boundaries. M Zhang et al [20] reported that addition of Y/Er and Zn to Mg-11Li, did not lead to the formation of the LPSO phase of the extruded alloys but increased the formation of intermetallic phases and a decrease in grain size. Improved strength was ascribed to refined dynamic crystallized grains and numerous intermetallic dispersions.…”
Section: Polymers Composites Alloys and Special Materialsmentioning
confidence: 99%